Beda Agama Bukan Penghalang dalam Kewarisan Menurut Hukum Perdata - Musa Azhari; Nur Sania Dasopang (Journal of Legal, Political, and Humanistic Inquiry, 2026)
This study examines the legal position of interfaith inheritance under Indonesian civil law, focusing on the principle that religious differences do not constitute an impediment to inheritance rights. Employing a normative legal research method, the study analyzes statutory regulations, doctrinal legal principles, and relevant court decisions governing inheritance under the Indonesian Civil Code (Burgerlijk Wetboek). The findings indicate that civil inheritance law is fundamentally based on blood relations and lawful marriage, rather than religious affiliation. As long as the legal requirements of heirs and inheritance objects are fulfilled, and no legal disqualifications apply, heirs of different religions remain entitled to inheritance rights. Judicial practice in general courts further demonstrates a consistent application of religious neutrality in inheritance disputes, reinforcing legal certainty and equality before the law. Although this approach differs from Islamic inheritance law, civil law serves as an inclusive legal framework that accommodates Indonesia’s pluralistic social structure. Consequently, civil inheritance law plays a crucial role in safeguarding civil rights and promoting justice within interfaith family relations.